Validation of mixed reality in planning orbital reconstruction with patient-specific implants - K. Dubron; E. Shaheen; R. Jacobs; C. Politis; R. Willaert (Scientific Reports)
Abstract This study aims to evaluate and compare the usability and performance of mixed reality (MR) technology versus conventional methods for preoperative planning of patient-specific reconstruction plates for orbital fractures. A crossover study design was used to compare MR technology with conventional three-dimensional (3D) printing approaches in the planning of maxillofacial traumatology treatments. The primary focus was on user-friendliness and the accuracy of patient-specific reconstruction planning. Secondary outcomes included investigating time differences between the two approaches and evaluating the potential effects on the learning curve. Participants were asked to complete questionnaires assessing various aspects, such as visualization, interaction, segmentation, treatment planning, and evaluation. Objective endpoints were evaluated blindly, while subjective endpoints were analyzed through a double-blind process. The total workflow time for MR technology was significantly shorter compared to the conventional method. Moreover, treatment planning using MR was significantly more accurate (p = .028), with participants reporting a higher mean global satisfaction score compared to the conventional group (80.6% vs. 72.5%). This study sheds light on the potential benefits of employing MR technology in maxillofacial orbital reconstruction. This preoperative method allows for faster and more precise design of patient-specific implants for orbital reconstruction, potentially leading to improved long-term cost-effectiveness.